Building the "Golden Generation": Understanding the Drivers of Investment Behavior in Gen Z and Millennial Women - Erna Apriani; Widiastuti; Nani Hartati; Rina Nurjanah; Abdul Latif (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to analyze the influence of financial knowledge and personality traits on the investment behavior of Gen Z and Millennial women with education level serving as a mediating variable.Method: The research employs Structural Equation Modeling (SEM) using SmartPLS software. The study sample includes Gen Z and Millennial women in Bekasi Regency. A purposive sampling technique was used, combining online and direct questionnaire distribution methods as well as interviews. A total of 100 respondents were selected for the study.Result: The findings indicate that financial knowledge does not directly impact investment behavior or education level. However, personality traits significantly influence both investment behavior and education level. Additionally, education level significantly affects investment behavior. While education level does not mediate the relationship between financial knowledge and investment behavior, it does mediate the relationship between personality traits and investment behavior.Practical Implications for Economic Growth and Development: This research underscores the importance of financial knowledge for Gen Z and Millennial women, particularly as Gen Z is poised to become the "golden generation" by 2045. By fostering sound financial management practices through financial knowledge and personality traits, individuals can effectively convert income into long-term assets through various investment instruments. This, in turn, contributes to sustainable economic development and growth.